Current status of knowledge, attitude, and perspective of dental practitioners toward cone beam computed tomography: A survey - Amita Aditya; Shailesh Lele; Priyam Aditya (Wolters Kluwer Medknow Publications, 2015)
Context of the Study: In India, cone-beam computed tomography (CBCT) has lately gained popularity as preferred imaging modality by the dental practitioners in recent times. However, CBCT is included neither in the undergraduate nor the Postgraduate dental curriculum. There is also a lack of any standardized training modules on CBCT. Many CBCT imaging centers are being established in various cities of India lately; however optimal use of this technique cannot be assured without assessing the attitude and present status of knowledge of the dental practitioners in this field. This shall warranty some remedial steps; in case a gap in knowledge is identified. Hence, this study was designed to analyze the current status of the knowledge, attitude and perspective of the dental practitioners in Pune, Maharashtra toward the use of CBCT. Materials and Methods: A survey was conducted among dental specialists, using a structured questionnaire. This was complemented with the opinion of the experts in the field of Oral Radiology. Results: The study results indicate that there is a definite gap in knowledge of CBCT applications among the dental specialists. The dental specialists themselves feel that there is a lack of awareness as well as training in this field, and strongly perceive a need for the same. Even the experts in the field of oral radiology strongly agree educational strategies must be developed for training in CBCT. Introduction of training in CBCT at undergraduate as well as Postgraduate level, and developing well-structured training modules shall ensure that dental specialists use this technique in an efficient way to improve the accuracy and reliability of Oral and Maxillo-facial diagnosis, treatment planning and outcomes.